Complete Chloroplast Genome Sequence of Chinese Lacquer Tree (Toxicodendron vernicifluum, Anacardiaceae) and Its Phylogenetic Significance. (30th January 2020) - Wang, Lu; He, Na; Li, Yao; Fang, Yanming; Zhang, Feilong
Abstract : Chinese lacquer tree ( Toxicodendron vernicifluum ) is an important commercial arbor species widely cultivated in East Asia for producing highly durable lacquer. Here, we sequenced and analyzed the complete chloroplast (cp) genome of T. vernicifluum and reconstructed the phylogeny of Sapindales based on 52 cp genomes of six families. The plastome of T. vernicifluum is 159, 571 bp in length, including a pair of inverted repeats (IRs) of 26, 511 bp, separated by a large single-copy (LSC) region of 87, 475 bp and a small single-copy (SSC) region of 19, 074 bp. A total of 126 genes were identified, of which 81 are protein-coding genes, 37 are transfer RNA genes, and eight are ribosomal RNA genes. Forty-nine mononucleotide microsatellites, one dinucleotide microsatellite, two complex microsatellites, and 49 long repeats were determined. Structural differences such as inversion variation in LSC and gene loss in IR were detected across cp genomes of the six genera in Anacardiaceae. Phylogenetic analyses revealed that the genus Toxicodendron is closely related to Pistacia and Rhus . The phylogenetic relationships of the six families in Sapindales were well resolved. Overall, this study providing complete cp genome resources will be beneficial for determining potential molecular markers and evolutionary patterns of T. vernicifluum and its closely related species.